2010
DOI: 10.1007/s10943-009-9319-x
|View full text |Cite
|
Sign up to set email alerts
|

Theory in Religion, Aging, and Health: An Overview

Abstract: This paper provides an overview of theory in religion, aging, and health. It offers both a primer on theory and a roadmap for researchers. Four “tenses” of theory are described—distinct ways that theory comes into play in this field: grand theory, mid-range theory, use of theoretical models, and positing of constructs which mediate or moderate putative religious effects. Examples are given of both explicit and implicit uses of theory. Sources of theory for this field are then identified, emphasizing perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 58 publications
1
32
0
4
Order By: Relevance
“…The mediating role of SPS has long been recommended and examined in the literature on older adults ' well-being ( Newsom & Schulz, 1996 ;Thielmann & Conner, 2009 ) . However, the study ' s fi ndings regarding the mediation by forgiveness and SPS affi rm that REL is associated with well being through multiple mechanisms ( Levin et al, 2011 ;Steger & Frazier, 2005 ). For example, Allen and colleagues (2008) in their study of REL /spirituality and mental health among older inmates reviewed argument of Ellison (1994) regarding the pathways through which REL might infl uence mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mediating role of SPS has long been recommended and examined in the literature on older adults ' well-being ( Newsom & Schulz, 1996 ;Thielmann & Conner, 2009 ) . However, the study ' s fi ndings regarding the mediation by forgiveness and SPS affi rm that REL is associated with well being through multiple mechanisms ( Levin et al, 2011 ;Steger & Frazier, 2005 ). For example, Allen and colleagues (2008) in their study of REL /spirituality and mental health among older inmates reviewed argument of Ellison (1994) regarding the pathways through which REL might infl uence mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The associations among religiosity (REL) , forgiveness, social provisions (SPS) and outcomes of mental and physical well-being have been well documented ( Koenig, 2008 ;Krause, 2008 ;Levin, Chatters, & Taylor 2011 ) as have the resulting clinical and applied implications ( Baetz & Toews, 2009 ;Hybels, Blazer, George, & Koenig, 2012 ;Sperry, Hoffman, Cox, & Cox, 2007 ). Koenig, McCullough, and Larson (2001) investigated the results of 100 studies and confi rmed the link between religious involvement and positive outcomes of mental health including happiness, positive affect, and life satisfaction among others.…”
mentioning
confidence: 99%
“…Because of its focus on the ways religion expresses itself in particular life situations, religious coping may add important information of religion and its links to health and wellbeing, especially among people facing critical problems in life. That dispositional religiousness and religious coping associated with both mental and physical health has been firmly established within the scientific literature (Koenig 2008, Levin et al 2011), particularly in the context of adversity (Ai & Park 2007, Linley & Joseph 2004). In general, the effects tend to be positive, including lower levels of psychological distress and depressive symptoms, better quality of life, and decreased morbidity and mortality ( Relative to less religious or nonreligious people, those who are religious tend to be more socially active and have higher levels of perceived social support and optimism (Ai & Park, 2007;Chan et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, leaders in faith communities often view health ministries as one aspect of their mission and obligation to care for others, that is, as a form of obedience to their vocation (REM personal communication). Over the past two decades, literature reviews have shown the relationships between religious variables and psychosocial and health-related outcomes in gerontological research (Levin & Chatters, 2011). For instance, a review of church-based health promotion (CBHP) programs by Campbell, Carr, Blackeney, Resnicow, and Baskin (2007) focused on two review papers by DeHaven, Hunter, Wilder, Walton, and Berry (2004) and Chatters, Levin, and Ellison (1998).…”
Section: Introductionmentioning
confidence: 99%